Analisis Indeks Kepuasan Masyarakat dan Faktor yang Mempengaruhi Layanan Keimigrasian di Kantor Imigrasi Kelas I Khusus TPI Surabaya (International Forum of Researchers and Lecturers, 2025)
Immigration services are a crucial part of public administration, playing a significant role in population mobility and immigration permit management. Evaluating public satisfaction with immigration services is essential to ensure optimal service quality. This study aims to analyze the level of public satisfaction and the key factors contributing to satisfaction with services at the Class I Special Immigration Office TPI Surabaya. A quantitative approach with a survey method was used to collect data from 1937 respondents who had received immigration services. Data analysis was conducted using the Public Satisfaction Index (IKM) technique and factor analysis with IBM SPSS 26 to identify dominant variables. The results indicate that immigration services received a high IKM score, though certain indicators require improvement, such as procedural clarity, processing time efficiency, and infrastructure. Factor analysis reveals that information availability, service fees, and officer responsiveness are the primary factors influencing public satisfaction. Based on these findings, enhancing service transparency, digitizing administrative processes, and optimizing the complaint management system are recommended strategies. The implementation of data-driven service improvements is expected to enhance immigration service quality and strengthen public trust in immigration institutions.